Exosomes and mimics as novel delivery platform for cancer therapy - Yang, Fuxu; Wang, Mingyue; Guan, Xingang (Frontiers in Pharmacology, 2022)
Exosomes are nano-sized biological extracellular vesicles transmitting information between cells and constituting a new intercellular communication mode. Exosomes have many advantages as an ideal drug delivery nanocarrier, including good biocompatibility, permeability, low toxicity, and low immunogenicity. Recently, exosomes have been used to deliver chemotherapeutic agents, natural drugs, nucleic acid drugs, and other antitumor drugs to treat many types of tumors. Due to the limited production of exosomes, synthetic exosome-mimics have been developed as an ideal platform for drug delivery. This review summarizes recent advances in the application of exosomes and exosome-mimics delivering therapeutic drugs in treating cancers.